Synthesis of Chalcone Derivatives and Their in vitro Anticancer Test Against Breast (T47D) and Colon (WiDr) Cancer Cell Line - Chairil Anwar; Yogo Dwi Prasetyo; Sabirin Matsjeh; Winarto Haryadi; Eti Nurwening Sholikhah; Nendrowati Nendrowati (Universitas Gadjah Mada, 2018)
The synthesis of chalcone derivatives as target compounds and anticancer test against breast (T47D) and colon (WiDr) cell line had been performed. The synthesis was performed by Claisen-Schmidt condensation by using acetophenone and benzaldehyde derivatives. The anticancer activity test of chalcone derivatives was carried out by MTT assay against T47D and WiDr cell lines. The synthesis was started by reacting 4-hydroxyacetophenone and benzaldehyde derivatives such as p-anisaldehyde (chalcone A [(E)-4'-hydroxy-4-methoxychalcone]), veratraldehyde (chalcone B [(E)-4'-hydroxy-3,4-dimethoxychalcone]), 4-chlorobenzaldehyde (chalcone C [(E)-4'-hydroxy-4-chlorochalcone]) and 2,4-dihydroxyacetophenone with 4-chlorobenzaldehyde (chalcone D [(E)-2',4'-dihydroxy-4-chlorochalcone]) in methanol as solvent. The synthesis was carried out in alkaline condition (KOH) by stirring the mixture at room temperature for 48 h. The structures of products were identified by FTIR, GC-MS, 1H- and 13C-NMR spectrometers. The results showed that the chalcone derivatives (A-D) were yielded in 96; 97; 96; and 93%, respectively as yellow solid. The anticancer test indicated that the chalcone D was the most active towards T47D cell line with IC50 of 42.66 μg/mL and the chalcone C was the most active against WiDr cell line with IC50 of 20.42 μg/mL.